2014
DOI: 10.1149/06406.0977ecst
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Epitaxial Si:C:P and Si:P Layers for Source/Drain Formation in Advanced Bulk FinFETs

Abstract: Uniaxial stressors have received much interest over the last few years as a method to enhance carrier mobility and, hence, drive current with minimal modification to the structure of the transistor. However, the shift in device design to complex structures with multiple crystallographic orientations like advanced bulk-FinFETs has significantly complicated the incorporation of mobility enhancing stressors. For the n-FinFET in particular, it turns out that the crystal quality and growth rate of Si:P and Si:C:P f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 12 publications
6
48
0
Order By: Relevance
“…At the same time, it will be shown that larger C-related clusters give rise to a deeper band of hole traps closer to the epitaxial interface. This can partly explain the observed loss in strain of the stressor layer after annealing [6], [13]. …”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…At the same time, it will be shown that larger C-related clusters give rise to a deeper band of hole traps closer to the epitaxial interface. This can partly explain the observed loss in strain of the stressor layer after annealing [6], [13]. …”
Section: Resultsmentioning
confidence: 87%
“…[4], [5] and [6]. Different device structures have been utilized to enable DLTS: either a p-n junction [4], a Metal-Oxide-Semiconductor (MOS) capacitor, based on Al2O3 gate dielectric or an Al Schottky barrier, evaporated on the Si:C epi layer.…”
Section: Methodsmentioning
confidence: 99%
“…In the experiment, P ion implanted (P I/I) Si substrates with N d of 2.0 Â 10 18 , 1.5 Â 10 19 , 7.0 Â 10 19 , and 2.8 Â 10 20 cm À3 were prepared on 300 mm Si wafers. P in situ doped epitaxial Si substrates (Si:P) 41 with high N d of 3.0 Â 10 20 , 8.0 Â 10 20 , and 9.0 Â 10 20 cm À3 were also prepared. Circular transmission line models (CTLM) and multiring CTLM (MR-CTLM) were fabricated for q c extraction: CTLM applies to a large range of q c between 10 À8 and 10 À1 XÁcm 2 , 42 while MR-CTLM is used to accurately determine ultralow q c from 10 À9 to 10 À7 XÁcm 2 .…”
Section: Contact Resistivities Of Metal-insulator-semiconductor Contamentioning
confidence: 99%
“…2, ultrahigh N d approaching 1 Â 10 21 cm À3 is achievable for n-Si. 41 With rare earth silicides as contact metal, low / b $ 0.3 eV have been demonstrated for MS contacts. 49,50 For MIS contacts, as shown in Fig.…”
Section: Contact Resistivities Of Metal-insulator-semiconductor Contamentioning
confidence: 99%
“…At the same time, keeping an as high as possible active P concentration is essential to reduce the contact resistance. 6,12 It has been observed in the past that the application of a postdeposition laser anneal (LA) increases the active P doping level 13 but at the same time results in lower layer stress, 12 suggesting the loss of substitutional carbon. This can happen through the formation of interstitial carbon (C i ) which is highly mobile even at room temperature (RT).…”
mentioning
confidence: 99%